Costs of colorectal cancer in different states of the disease. (April 2015) - Färkkilä, Niilo; Torvinen, Saku; Sintonen, Harri; Saarto, Tiina; Järvinen, Heikki; Hänninen, Juha; Taari, Kimmo; Roine, Risto P.
Abstract Objectives. This cross-sectional study estimates the resource use and costs among prevalent colorectal cancer (CRC) patients in different states of the disease. Methods. Altogether 508 Finnish CRC patients (aged 26–96; colon cancer 56%; female 47%) answered a questionnaire enquiring about informal care, work capacity, and demographic factors. Furthermore, data on direct medical resource use and productivity costs were obtained from registries. Patients were divided into five mutually exclusive groups based on the disease state and the time from diagnosis: primary treatments (the first six months after the diagnosis), rehabilitation, remission, metastatic disease, and palliative care. The costs were calculated for a six-month period. Multivariate modeling was performed to find the cost drivers. Results. The costs were highest during the primary treatment state and the advanced disease states. The total costs for the cross-sectional six-month period were €22 200 in the primary treatment state, €2106 in the rehabilitation state, €2812 in the remission state, €20 540 in the metastatic state, and €21 146 in the palliative state. Most of the costs were direct medical costs. The informal care cost was highest per patient in the palliative care state, amounting to 33% of the total costs. The productivity costs varied between disease states, constituting 19–40% of the total costs, and were highest in the primary treatment state. Conclusions. The first six months after the diagnosis of CRC are resource intensive, but compared with the metastatic disease state, which lasts on average for 2–3 years, the costs are rather modest. Informal care constitutes a remarkable share of the total costs, especially in the palliative state. These results form a basis for the evaluation of the cost effectiveness of new treatments when allocating resources in CRC treatment.